PENANGANAN KONFLIK AGAMA DI KOTA JAMBI BERBASIS KEBIJAKAN PUBLIK (TAJDID: Jurnal Ilmu Ushuluddin, 2021)
This research seeks to analyze the policy of Jambi City Government in handling of religious conflict, especially the establishment of worship place, in Jambi City. This research adopted qualitative approach with case study of research type. Jambi City is a religiously plural area that has experienced conflicts over the establishment of worship places. Because of this, the Jambi City Government issued a policy of intensive coordination with religious leaders, peaceful conflict resolution, verification of permits for worship places and development of tolerance villages. These policies are intended so that religious conflicts that commonly occur in plural societies do not continue and threaten the harmonization of society. This research is scientifically and practically significant since it: Contributes to enriching the theoretical aspect of the academic studies on public policy in the reality of the government’s role and its use of this model in managing public areas, especially in religion. This research completely discussed the perceptions about the tracks of the government’s role and the extent of use of realism in public policy, especially in the religious conflict. As well as define the realist conditions, means, methods, and tools adopted by the researchers in strengthening the public policy theory to achieve study of government’s role in handling public problems, especially in religious conflict.Penelitian ini berupaya menganalisis kebijakan Pemerintah Kota Jambi dalam penanganan konflik agama khususnya pendirian rumah ibadah di Kota Jambi. Penelitian ini mengadopsi pendekatan kualitatif dengan jenis penelitian studi kasus. Kota Jambi merupakan daerah yang majemuk beragama yang mengalami konflik pendirian rumah ibadah. Karena itu, Pemerintah Kota Jambi mengeluarkan kebijakan koordinasi intensif dengan tokoh agama, penyelesaian konflik secara damai, verifikasi izin tempat ibadah dan pengembangan kampung toleransi. Kebijakan tersebut dimaksudkan agar konflik keagamaan yang lazim terjadi dalam masyarakat majemuk tidak berlanjut dan mengancam harmonisasi masyarakat. Penelitian ini signifikan secara ilmiah dan praktis karena: Berkontribusi untuk memperkaya aspek teoretis kajian akademik tentang kebijakan publik dalam realitas peran pemerintah dan penggunaan model ini dalam mengelola ruang publik, khususnya dalam bidang agama. Penelitian ini secara lengkap membahas persepsi tentang jejak peran pemerintah dan sejauh mana penggunaan realisme dalam kebijakan publik, khususnya dalam konflik agama. Serta menentukan kondisi realis, cara, metode, dan perangkat yang digunakan peneliti dalam memperkuat teori kebijakan publik untuk mencapai kajian peran pemerintah dalam menangani masalah publik, khususnya dalam konflik agama.